If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42g + -45g + (-93) = -12 42g + -45g + -93 = -12 Reorder the terms: -93 + 42g + -45g = -12 Combine like terms: 42g + -45g = -3g -93 + -3g = -12 Solving -93 + -3g = -12 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '93' to each side of the equation. -93 + 93 + -3g = -12 + 93 Combine like terms: -93 + 93 = 0 0 + -3g = -12 + 93 -3g = -12 + 93 Combine like terms: -12 + 93 = 81 -3g = 81 Divide each side by '-3'. g = -27 Simplifying g = -27
| z*z= | | 13-6x=-38 | | 91v-16v-61v-12v-v=95 | | 16y-24=4y | | 16z-48=4z | | 51=3*3+2*3*h | | X^2+9x-3=5x-7 | | 3x-(x+1)=6m+1 | | 2m+7+3m=-33 | | 6.25y=9 | | 73-x=2x+3 | | 3000=300(10+x) | | [x-2]=-4 | | 2a-38a+43a+(-29a)=66 | | 1.26=2z-8 | | 3000=300x+3000 | | -5.75y=9 | | 3(95-6x)=1x-152 | | 2x+(1-3x)=-7 | | e^3x-1=(e^6)-x | | (0.5x-3)(0.6x+3)=0 | | 27k+(-24k)=24 | | 7x-7=9x-3x | | 5x+7=-7 | | 16.1=5x+5.6 | | (x-3)*(x-2)=q | | -4a-50a+6a-(-31a)-(-13a)-17=19 | | x+(3-5x)=-9 | | 7x-1=7+5x | | 12(1)+3y=15 | | x+7*4=-3 | | 12(-1)+3y=15 |